Business data processing & programming - Gregory, Robert H. (Wadsworth Pub. Co., 1963)
Will be shipped from US. Used books may not include companion materials, may have some shelf wear, may contain highlighting/notes, may not include CDs or access codes. 100% money back guarantee.